Ecological patterns in the Porto-Novo Lagoon (Benin, West Africa): A review with implications for SDG 6.3.2 and EU-WFD readiness toward ecological status classification - Metogbe Belfrid Djihouessi; Gildas Djidohokpin; Romaric Christian Marc Hekpazo; Akilou Amadou Socohou; Lewis Zounon; Zacharie Sohou; Abou Youssouf; Martin Pépin Aina (PLoS ONE, 2026)
Urban tropical lagoons provide vital services yet face nutrient loading, macrophyte blooms, and episodic hypoxia. This scoping review compiles four decades of hydromorphological, physico-chemical, and biotic evidence for Benin’s Porto-Novo Lagoon and assesses readiness for UNEP SDG 6.3.2 Level 1 reporting and a EU Water Framework Directive (WFD)-oriented exploratory gap analysis rather than an operational assessment. The lagoon is strongly seasonal, shaped by Ouémé inflows and marine intrusions; eutrophication symptoms and floating macrophytes have intensified since the 1980s. Core SDG 6.3.2 Level 1 parameter-group proxies (pH, DO, EC, PO₄-P) are moderately covered, but nitrogen evidence is scarce and time-continuous station series are rare. A completeness audit indicates about 60% coverage for SDG-related variables and lower maturity for WFD biological elements, meaning that formal SDG compliance-based classification (“good and not good”) and any Ecological Quality Ratios based WFD ecological status classification cannot be derived from the compiled literature. Near-term priorities are therefore framed as readiness building, focused on strengthening consistent in situ series for the SDG core groups; context-adapted complementary sources may support gap filling and interpretation but do not substitute Level 1 requirements. For WFD, the evidence base highlights prerequisites for future work, including transitional water-body delimitation and type-specific reference conditions, standardised Biological Quality Elements monitoring, and priority-substance surveillance. Comparison with Ébrié, Lekki, and Sakumo II underscores the value of governance and monitoring designs that avoid data fragmentation.